HOW ARE YOU FEELING TODAY? – Gaps and opportunities in capturing patient reported outcomes (PROs) in Pediatric Cancer Care - Anna Zettl; Hannah Gsell; Karolina Maślak; Antti Karjalainen; Ulrike Leiss; Anita Kienesberger; Carina Schneider (EJC Paediatric Oncology)
Including children's perspectives in healthcare and clinical trials, particularly in pediatric oncology, is critical to promoting child-centered care. Research has shown that even very young children can understand complex medical concepts, highlighting the psychological and practical benefits of involving children in their care. Patient-Reported Outcome Measures (PROMs) play a critical role in capturing young patients' insights about their symptoms and well-being. This enables individualized care and an improvement in quality of life. Despite their potential, the use of PROMs in pediatric oncology faces significant challenges, including age-related barriers to understanding and the exclusion of cognitively impaired children. PROMs, when used effectively, can empower patients, improve communication and influence clinical decisions in favor of young patients. However, their relevance depends on the active participation of patients and caregivers in their design and use. PROMs also need to be further developed in the area of survivorship to close gaps in long-term care where many physical and psychological problems otherwise go unrecognized. Tailoring PROMs to patients' needs ensures that every patient, regardless of age or neurocognitive ability, contributes to a comprehensive understanding of the impact of treatment. Incorporating PROMs into routine care and clinical trials, supported by patient advocacy and systematic implementation, can address critical gaps. This approach ensures that pediatric oncology adapts to the diverse needs of children and survivors to improve long-term outcomes and promote a truly patient-centered model.